Fully Enhanced Homomorphic Encryption algorithm of MORE approach for real world applications. (June 2017) - Hariss, Khalil; Noura, Hassan; Samhat, Abed Ellatif
Abstract: The design of a Homomorphic Encryption (HE) algorithm that allows computation over the encrypted data is required in real world modern applications to preserve the privacy. Such applications include Cloud Computing, shared storage, processing resources, etc. The existing solutions are not practical for real world applications. Asymmetric approaches suffer from high computation overhead, while symmetric approaches suffer from low immunity against attacks such as chosen and known plaintext attack. In this paper, we consider symmetric approaches and we focus on Matrix Operation for Randomization and Encryption (MORE) approach to build a new algorithm overcoming the drawbacks of MORE. The proposed algorithm is explained in details and evaluated. The security performance results show that the proposed approach can prevent the strong attacks without degradation of the system performances in term of latency and energy consumption.